Hematopoietic stem cell transplantation positively affects the natural history of cancer in Nijmegen breakage syndrome - Wolska-Kusnierz, Beata; Greil, Johann (Clinical cancer research, 2021)
Purpose: Nijmegen breakage syndrome (NBS) is a DNA repair disorder with a high predisposition to hematologic malignancies. - Experimental Design: We describe the natural history of NBS, including cancer incidence, risk of death, and the potential effectiveness of hematopoietic stem cell transplantation (HSCT) in preventing both pathologies: malignancy and immunodeficiency. - Results: Among 241 patients with NBS enrolled in the study from 11 countries, 151 (63.0%) patients were diagnosed with cancer. Incidence rates for primary and secondary cancer, tumor characteristics, and risk factors affecting overall survival (OS) were estimated. The cumulative cancer incidence was 40.21% ± 3.5% and 77.78% ± 3.4% at 10 years and 20 years of follow-up, respectively. Most of the tumors n = 95 (62.9%) were non-Hodgkin lymphomas. Overall, 20 (13.2%) secondary malignancies occurred at a median age of 18 (interquartile range, 13.7-21.5) years. The probability of 20-year overall survival (OS) for the whole cohort was 44.6% ± 4.5%. Patients who developed cancer had a shorter 20-year OS than those without malignancy (29.6% vs. 86.2%; P < 10−5). A total of 49 patients with NBS underwent HSCT, including 14 patients transplanted before malignancy. Patients with NBS with diagnosed cancer who received HSCT had higher 20-year OS than those who did not (42.7% vs. 30.3%; P = 0.038, respectively). In the group of patients who underwent preemptive transplantation, only 1 patient developed cancer, which is 6.7 times lower as compared with nontransplanted patients [incidence rate ratio 0.149 (95% confidence interval, 0.138-0.162); P < 0.0001]. - Conclusions: There is a beneficial effect of HSCT on the long-term survival of patients with NBS transplanted in their first complete remission of cancer.
Published OnlineFirst October 20, 2020
Gesehen am 13.04.2021